Design and experiment of an upper-side-discharge straw-returning and bundle self-unloading integrated corn residual film recycling machine - Liu, Xiaolong; Zhao, Wuyun; Zhang, Hua; Wang, Guanping; Sun, Wei; Dai, Fei; Li, Hui; Xin, Shanglong (International Journal of Agricultural and Biological Engineering, 2023)
Due to the arid climate, flat terrain, certain irrigation sources and high popularization of mechanical harvest in Hexi Irrigation Area of Gansu Province, the widely adopted half film-flat-mulching for corn cultivation faces serious adverse situations, such as high soil compactness, strong film-soil adhesion, significant straw stubble and thick covering accumulation on film. Therefore, a new kind of segmented combination upper-side-discharge straw-returning and bundle self-unloading integrated corn residual film recycling machine was proposed. The scheme was characterized by small volume, low resistance, low complexity and film-impurities twice separation. It was constructed based on the concept of module subsection combination. It was composed of film surface straw cleaning device and the followed residual film recycling machine, in terms of function, any usage requirements of separate and joint operations can be satisfied. The film surface straw cleaning device is responsible for the removal of vertical corn straw and ground covering beyond the film. Although its stubble cutter roller obtuse-angle L-shaped blades paired single-helix arrangement is simple, it runs smoothly and the straw crushing effect is good enough. The layout that upper-side-discharge straw-returning cross-range screw conveyor auger is back and beyond the stubble cutter roller, eliminates the common connecting transportation mechanism between crushing and straw-returning section, so that, the system structure can be optimized and the efficiency has been significantly improved. The integrated residual film recycling machine is composed of triangular pyramid arc two-stage wing (TPATSW) type film lifting shovel, rod-tooth-belt type film-impurities separation device and semi-enclosed shaftless bundle film collector. Among them, TPATSW type film lifting shovel has good corn root whisker cutting effect, low soil contact resistance and small soil congestion area, but its ability to lift film is strong, more importantly, the special segmented configuration of shovel handle and the body, shortens the overall machine length significantly. For semi-enclosed shaftless bundle film collector, however, a new scheme of eight sub-rolls rotate in the same direction, to roll the residual film into a bundle is innovatively adopted. Under its own parameters, the system has the lowest sub-roll rotation speed that can bundle the residual film without shaft inside the film collecting chamber, rather than on any sub-roll itself. The gap between the sub-rolls can separate impurities for the second time. After the film collection reaches the standard, the film collector can dump the residual film directly, which is simple and efficient. The field orthogonal test data of the prototype show that, the optimal parameter combination is: film lifting shovel earth angle is 30°, its operation depth is 50 mm and the machine forward speed is 5.0 km/h. The average residual film recycling rate and the crushed straw qualified rate under the optimal parameters are 84.9% and 90.3% respectively, which can meet the requirements of the national and industrial standards. The research solved the passive situation that there was no matching equipment for the recycle of residual film in corn field in Hexi Irrigation Area effectively.Keywords: corn, segmented combination, film surface straw cleaning, straw-returning, TPATSW type film lifting shovel, film-impurities twice separation, semi-enclosed shaftless bundle film collector, self-unloadingDOI: 10.25165/j.ijabe.20231605.7995Citation: Liu X L, Zhao W Y, Zhang H, Wang G P, Sun W, Dai F, et al. Design and experiment of an upper-side-discharge straw-returning and bundle self-unloading integrated corn residual film recycling machine. Int J Agric & Biol Eng, 2023; 16(5): 61–70.